Core-shell ZnO/SnO2 Nanorods: two-step Synthesis and Enhanced Ethanol Sensing Performance - Sun, Guang; Zhang, Saisai; Li, Yanwei; Qi, Fengxiao; Chen, Honglin; Zhang, Zhanying (Current Nanoscience, 2015)
Core-shell ZnO/SnO2 nanorods (NRs) were successfully synthesized via a facile two-step synthesis route. ZnO NRs (core) with the diameter about 300–800 nm and the length about 2-2.5 µm were first synthesized via a hydrothermal route, and then a continuous SnO2 layer (shell) with the thickness about 20-25 nm was easily coated on the ZnO NRs via a solvothermal route. Compared with pure ZnO NRs and SnO2 nanoparticles (NPs), the ZnO/SnO2 core-shell NRs show an obvious enhancement in gas sensing performance. The response of the sensor based on as-prepared ZnO/SnO2 core-shell NRs to 100 ppm ethanol is as high as 29.5 at 340 °C, and the response and recovery time are found to be about 18 s and 11 s, respectively. The gas sensing mechanism of the ZnO/SnO2 core-shell NRs was discussed in relation to ZnO/SnO2 heterojunctions.
Keywords: ethanol sensors